Nanoparticle mediated drug delivery of rolipram to tyrosine kinase B positive cells in the inner ear with targeting peptides and agonistic antibodies - Glueckert, Rudolf (Frontiers Media S.A., 2015)
Aim: Systemic pharmacotherapies have limitation due to blood-labyrinth barrier, so local delivery via the round window membrane opens a path for effective treatment. Multifunctional nanoparticle (NP)-mediated cell specific drug delivery may enhance efficacy and reduce side effects. Different NPs with ligands to target TrkB receptor were tested. Distribution, uptake mechanisms, trafficking, and bioefficacy of drug release of rolipram loaded NPs were evaluated.